The Need to Give Gratuitously: A Relevant Concept Anchored in Catholic Social Teaching to Envision the Consumer Behavior - Peyrelongue, Bénédicte de; Masclef, Olivier; Guillard, Valérie (2017)
The “gift exchange theory” articulated by Marcel Mauss, along with his core concept of a threefold obligation (giving/receiving/returning), is the dominant theoretical framework used to explain the majority of gift issues in marketing. This perspective assumes that some interest always lies behind gifts, such that a gift always implies a counterpart of receiving something in return. Despite the relevance of this approach in understanding the day-to-day consumer behavior, this paper presents empirical cases where the consumer is also able to give freely, that is to say without implying a counterpart or even expecting it. To explain those empirical cases, we mobilize a key teaching of the Catholic Church: the “gratuitous gift” and then introduce the concept of the “need to give.” We show that gratuitousness is a relevant concept to understand most of gifts made by consumers, and we develop the normative aspect of gratuitous gift for ethical marketers (i.e., what ethical marketers should consider to understand consumers properly and in a more humanistic way). We also show that Catholic Social Teaching offers an appropriate anthropology to understand consumer behaviors motivated by this need for gratuitousness. To conclude, we propose further avenues of research.
Keywords: Consumer behavior; Need to give gratuitously; Gratuitousness; Gift; Catholic Social Teaching